Resilience and Women in the Maldives post-disaster: A case study - Athifa, Mariyam (Curtin University, 2020)
An exploration of factors that contributed to women’s experience following a disaster using qualitative methods in a discipline-configurative case study design. Using a conceptual framework of resilience, the complex social phenomenon of the Maldivian women’s experiences of the December 2004 tsunami disaster is described, analyzed and explained with a resultant model for resilient communities highlighting that control and coherence are fundamental elements that help to achieve connectedness to bounce back from disasters.